(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective : This study aimed to investigate the relationship between hematological parameters, serum iron, and vitamin B12 levels in adult hospitalized Palestinian patients infected with Helicobacter pylori.Methods : The collected the data, prospectively, all H.Pylori cases admitted in lab private during the study period between April 2022 and August 2022. During the five months , (30) cases with H.pylori and (30) control . patients had H.pylori positive. laboratory analysis of inflammatory indices and organ function was accomplished for the sum total of cases and controlsRESULT : The results in this research showed that there is a highly significant between stomach germs(H. pylori), iron, ferritin and vitamin B12, and there is non-significant with vitamin D.